The Atlantic : A Preliminary Account of the General Results of the Exploring Voyage of HMS Challenger during the Year 1873 and the Early Part of the Year 1876 / Charles Wyville Thomson - THOMSON, Charles Wyville (Cambridge University Press, 2014)
...volume : ilus. ; 23 cm.